HAKIKAT PENDIDIKAN NILAI DAN MORAL DALAM MEMBENTUK GENERASI BERKARAKTER - Anjulin Yonathan Kamlasi; Fadil Mas’ud; Amanda M.J Laning; Diyah Khadijah Blegur; Donatus Ferdinando Kota; Gheanida J.J Funu; Leoni Elsa Noni Faot (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Values and moral education are essential for shaping a generation with character amidst the challenges of globalization and digitalization that threaten the moral integrity of Indonesia's youth. A 2024 report from the Ministry of Education, Culture, Research, and Technology (Kemendikbudristek) noted that 65% of adolescents experience value conflict due to exposure to social media, while Transparency International (2024) ranked Indonesia 110/180 on the Corruption Perception Index. This article examines the internalization of moral values through a holistic approach based on Pancasila, analyzes the strategic roles of families, schools, and communities, and develops effective implementation strategies toward the vision of a Golden Indonesia 2045.Using qualitative methods based on literature reviews and descriptive analysis, secondary data from education journals (2020-2025), UNESCO reports, and international case studies (Finland) were analyzed through thematic content analysis. Key findings indicate that education based on Pancasila and local wisdom can increase the integrity and social resilience of the younger generation by up to 30%, as evidenced by the Independent Curriculum. Key challenges, such as the influence of gadgets, are addressed through multi-stakeholder collaboration, digital ethical literacy, and project-based learning. The conclusion emphasizes the collective commitment of all parties to realizing the Pancasila Student Profile, which is devout, cooperative, and critical. Recommendations include national teacher training and empirical character indicators. This research contributes to the transformation of character education in Indonesia.